This Year’s Three UN Summits Set the Stage for COP30 to Transform Food Systems - Mukherji, Aditi; Masso, Cargele (2024)
This year has been a landmark one for climate and environment policy. Starting with the UN’s COP16 biodiversity talks in October, followed by the COP29 climate talks in November, and closing with the desertification COP16 in December, few years have offered such critical moments back-to-back.